2018
DOI: 10.1111/dpr.12381
|View full text |Cite
|
Sign up to set email alerts
|

Delivering development? Evidence on self‐help groups as development intermediaries in South Asia and Africa

Abstract: Donors and governments increasingly seek to deliver development projects through community‐based organizations such as self‐help groups (SHGs), but little is known about the effectiveness of such arrangements. This article briefly summarizes hypotheses regarding the effectiveness of interventions using SHGs and presents the results of an evidence review on the impacts of interventions delivered through SHGs on health, finance, agriculture and empowerment outcomes in South Asia and sub‐Saharan Africa. Though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 72 publications
(375 reference statements)
2
64
0
Order By: Relevance
“…More evidence on the impact of FOs is urgently needed for governments and donor organizations to identify effective interventions to achieve the SDGs, including target 2.1 to fight hunger, 2.3 to improve the income of smallholders and 2.4 to promote environmentally friendly agricultural practices and responses to climate change. Although several studies have reviewed the contributions of FOs towards those objectives, most have focused on a subset of FO types and/ or individual countries 12,21,22 . Many have not applied a systematic approach 23 .…”
mentioning
confidence: 99%
“…More evidence on the impact of FOs is urgently needed for governments and donor organizations to identify effective interventions to achieve the SDGs, including target 2.1 to fight hunger, 2.3 to improve the income of smallholders and 2.4 to promote environmentally friendly agricultural practices and responses to climate change. Although several studies have reviewed the contributions of FOs towards those objectives, most have focused on a subset of FO types and/ or individual countries 12,21,22 . Many have not applied a systematic approach 23 .…”
mentioning
confidence: 99%
“…Women's groups can be 'closed', i.e., restricted to members who fulfil specific criteria, for example, those who make financial contributions, or 'open' to all women and other community members, in which case they are akin to community groups. [6][7][8][9] Some community interventions use existing groups as a platform to share health information or seek to leverage group cohesion to improve members' health. 10 Others aim to improve population health through community mobilisation, defined as 'a capacity building process through which community members, groups or organizations plan, carry out, and evaluate activities in a participatory and sustained basis to improve their health and other conditions'.…”
mentioning
confidence: 99%
“…The results showed that participation in self-help groups improved savings rates and access to credit, facilitating investment in income-generating activities. Studies have shown similar results by showing that group members are more proactive in implementing IGAs(Gugerty et al 2019, Greaney et al 2013). …”
mentioning
confidence: 75%